Implementasi Pendidikan Akhlak dalam Membentuk Kepribadian Muslim Siswa di MI Ma’arif Kaliwiro Wonosobo - Sulton Isnawan; Muchotob Hamzah; Lilik Rochmad Nurcholisho (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research describes the implementation of moral education, determines the influence of moral education, as well as the variables that facilitate and hinder its implementation in developing Muslim personality at MI Ma'arif Kaliwiro. In this research, case study methodology is combined with qualitative research methods. Data collection methods include documentation, interviews and observation. This research found several findings: 1) Implementation of moral education such as shaking hands when arriving in the morning, reading Asmaul Husana, reading prayers at the start of the day, Dhuha prayers in congregation, and reading the Koran. 2) Increasing students' morals, as well as diligent prayer, discipline and obeying regulations is one of the benefits of moral education. 3) The role of the school principal, facilities and infrastructure, and motivation really support the implementation of moral education at MI Ma'arif Kaliwiro. In this case, there is a need for strong cooperation and accountability from the foundation, school principals, teachers, students, supporting facilities and infrastructure so that the moral education program can have maximum impact on the formation of Muslim students' personalities. The lack of student knowledge is one of the factors that causes moral education not to be implemented in forming the Muslim personality of MI Ma'arif Kaliwiro students.